Colorimetric detection method of formaldehyde in coal-based ethylene glycol

CN123008764APending Publication Date: 2026-10-30GUANGXI TEACHERS EDUCATION UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611210976.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-11
Publication Date
2026-10-30

AI Technical Summary

Technical Problem

甲醛作为一种具有挥发性和毒性的杂质,会严重影响乙二醇在聚酯级应用中的光学性能(如紫外透光率),进而影响产品质量

Benefits of technology

[0022]本发明利用巯基化氧化硅纳米颗粒催化靛蓝褪色,通过测定620纳米波长处反应前后的吸光度差值进行定量,在0.03至0.5 ppm范围内线性良好,检出限可达0.02871 ppm,能够满足煤基乙二醇中痕量甲醛的检测需求。通过反应前后差值测定,可有效抵消纳米颗粒光散射背景及基质干扰,无需离心过滤,简化了操作流程。针对煤基乙二醇高粘度特性,采用聚乙二醇对纳米颗粒进行预分散,可有效抑制颗粒团聚,确保其在静置反应过程中保持稳定悬浮状态,使前后吸光度测定时的散射背景一致。在此基础上,通过加入β-环糊精包合体系中游离的聚乙二醇,消除了其对反应速率的非特异性干扰,使平行样品的相对标准偏差由5.6%改善至2.1%,显著提升了检测精密度。加标回收率在98.0%至98.7%之间,表明该方法在煤基乙二醇基质中具有良好的准确性和重复性。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN123008764A_ABST
    Figure CN123008764A_ABST
Patent Text Reader

Abstract

The application discloses a colorimetric detection method of formaldehyde in coal-based ethylene glycol, and belongs to the technical field of coal chemical product quality analysis and detection. In view of the disadvantages of the existing detection method, such as complex operation and weak anti-interference ability in the high-viscosity and complex organic matrix of coal-based ethylene glycol, the method comprises the following steps: adding mercapto-silica nanoparticles into a to-be-detected sample, adding an indigo blue solution and adjusting the pH to 7.0-8.0, measuring the initial absorbance at 620 nm, standing for 25-35 minutes at room temperature to make the formaldehyde induce the fading of the indigo blue, re-measuring the absorbance, and calculating the absorbance drop value before and after the reaction, and then substituting the absorbance drop value into a linear regression equation between the formaldehyde concentration and the absorbance drop value, so as to obtain the formaldehyde concentration in the sample. The method can be used for rapid quantitative detection of trace formaldehyde in coal-based ethylene glycol, and is simple in operation and accurate and reliable in result.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of coal chemical product quality analysis and testing technology, specifically relating to a colorimetric quantitative detection method for formaldehyde in coal-based ethylene glycol based on a mercapto-modified silica nanoparticle and indigo colorimetric system, which is particularly suitable for the detection of trace formaldehyde residues in coal-based ethylene glycol products. Background Technology

[0002] Coal-to-ethylene glycol (CGE) is an important chemical process that has emerged in recent years as an alternative to petroleum-based routes. During the multi-step catalytic reaction of coal-derived syngas to form CGE, low-molecular-weight byproducts such as formaldehyde are often generated. Especially when the distillation or catalytic process is imperfect, formaldehyde can easily remain in the final product. As a volatile and toxic impurity, formaldehyde can severely affect the optical properties (such as UV transmittance) of CGE in polyester applications, thus impacting product quality. Traditional methods for formaldehyde detection, such as the AHMT colorimetric method, the phenol reagent method, and HPLC, suffer from drawbacks such as complex operation and weak anti-interference capabilities under the conditions of high viscosity and complex organic background in coal-based CGE. Therefore, there is an urgent need to develop a novel formaldehyde detection method with strong responsiveness suitable for coal-based CGE samples. Summary of the Invention

[0003] One object of the present invention is to solve at least the above-mentioned problems and to provide at least the advantages that will be described later.

[0004] Another objective of this invention is to provide a colorimetric detection method for formaldehyde in coal-based ethylene glycol. This method utilizes the selective interaction between mercapto-modified silica nanoparticles and formaldehyde to catalyze a fading reaction in indigo. By measuring the decrease in absorbance at 620 nm, it achieves rapid quantitative detection of trace formaldehyde in coal-based ethylene glycol, effectively eliminating interference from high-viscosity organic matrices. The detection limit reaches 0.02871 ppm, and the operation is simple and the results are stable and reliable.

[0005] This invention discloses a colorimetric detection method for formaldehyde in coal-based ethylene glycol, comprising the following steps:

[0006] Thiolized silica nanoparticles are added to the coal-based ethylene glycol sample to be tested. The amount of thiolated silica nanoparticles added is 5 mg to 15 mg per milliliter of the coal-based ethylene glycol sample to be tested, forming a first mixture.

[0007] An indigo solution with a concentration of 0.04 mmol / L to 0.06 mmol / L was added to the first mixture. The volume ratio of the coal-based ethylene glycol sample to the indigo solution was 1:1 to 2:1. The mixture was then thoroughly mixed to form a second mixture with a pH value of 7.0 to 8.0.

[0008] The initial absorbance A0 of the second mixture was measured at a wavelength of 620 nm using a UV-Vis spectrophotometer.

[0009] The second mixture was allowed to stand at room temperature for a total of 25 to 35 minutes to allow the formaldehyde in the second mixture to induce a fading reaction in indigo in the presence of the mercapto-modified silica nanoparticles.

[0010] Measure the absorbance A of the second mixture after it has been allowed to stand, and calculate the decrease in absorbance y = A0 - A;

[0011] Substituting the absorbance decrease value y into the linear regression equation between formaldehyde concentration and absorbance, the formaldehyde concentration in the coal-based ethylene glycol sample to be tested is calculated. The linear regression equation is y=a•c+b, where y is the absorbance decrease value at a wavelength of 620nm, c is the formaldehyde concentration, a is the slope, and b is the intercept.

[0012] Preferably, the thiolized silica nanoparticles are prepared by the following steps:

[0013] Silica nanoparticles with an average diameter of 10 nm to 20 nm were added to a mixed solvent composed of acetic acid, water, and anhydrous ethanol to form a nanoparticle suspension. The volume ratio of acetic acid, water, and anhydrous ethanol in the mixed solvent was 60:70:100. The amount of silica nanoparticles used to the mixed solvent was 4.0 g to 5.0 g of silica nanoparticles per 200 mL to 260 mL of the mixed solvent.

[0014] A mixture of 3-[2-(2-aminoethylamino)ethylamino]propyl-trimethoxysilane and (3-mercaptopropyl)trimethoxysilane is added to the nanoparticle suspension, wherein the molar ratio of 3-[2-(2-aminoethylamino)ethylamino]propyl-trimethoxysilane to (3-mercaptopropyl)trimethoxysilane is 10:1, and 0.30 mmol to 0.50 mmol of 3-[2-(2-aminoethylamino)ethylamino]propyl-trimethoxysilane and 0.030 mmol to 0.050 mmol of (3-mercaptopropyl)trimethoxysilane are added per gram of silica nanoparticles to form a reaction mixture;

[0015] The reaction mixture is heated to 70°C to 90°C and maintained for 36 to 60 hours to allow 3-[2-(2-aminoethylamino)ethylamino]propyl-trimethoxysilane and (3-mercaptopropyl)trimethoxysilane to undergo a hydrolysis-condensation reaction on the surface of the silica nanoparticles, thereby obtaining a functionalized nanoparticle suspension.

[0016] The solvent is removed from the functionalized nanoparticle suspension, the precipitate is collected, and the precipitate is washed sequentially with water and acetone. The washed precipitate is then dried at 60°C to 80°C to obtain the thiolized silica nanoparticles.

[0017] Preferably, the pH of the second mixture is adjusted to 7.0 to 8.0 using a phosphate buffer solution or a borate buffer solution.

[0018] Preferably, before adding the thiolized silica nanoparticles to the coal-based ethylene glycol sample to be tested, the thiolized silica nanoparticles are dispersed in a polyethylene glycol solution, wherein the number average molecular weight of the polyethylene glycol is 200 to 600, the mass fraction of the polyethylene glycol solution is 0.1% to 0.5%, and the volume ratio of the thiolized silica nanoparticles to the polyethylene glycol solution is 5 mg to 15 mg of thiolized silica nanoparticles dispersed per milliliter of the polyethylene glycol solution, forming a pre-dispersed nanoparticle suspension; the pre-dispersed nanoparticle suspension is then added to the coal-based ethylene glycol sample to be tested, wherein the volume ratio of the pre-dispersed nanoparticle suspension to the coal-based ethylene glycol sample to be tested is 1:1, forming the first mixture.

[0019] Preferably, after the second mixture is allowed to stand at room temperature for 15 to 20 minutes, a β-cyclodextrin solution is added to the second mixture, wherein the mass fraction of the β-cyclodextrin solution is 0.5% to 1.0%, and the molar ratio of the β-cyclodextrin to the polyethylene glycol in the second mixture is 0.2:1 to 2:1, and the mixture is allowed to stand for a total standing time of 25 to 35 minutes.

[0020] Preferably, the linear regression equation is obtained by fitting the standard curve of the batch and has the form y=a•c+b.

[0021] The present invention has at least the following beneficial effects:

[0022] This invention utilizes mercapto-modified silica nanoparticles to catalyze the decolorization of indigo. Quantification is achieved by measuring the difference in absorbance before and after the reaction at a wavelength of 620 nm. The method exhibits good linearity within the range of 0.03 to 0.5 ppm, with a detection limit of 0.02871 ppm, meeting the requirements for detecting trace formaldehyde in coal-based ethylene glycol. Measuring the difference before and after the reaction effectively offsets the light scattering background of the nanoparticles and matrix interference, eliminating the need for centrifugation and filtration, thus simplifying the operation. To address the high viscosity of coal-based ethylene glycol, polyethylene glycol is used to pre-disperse the nanoparticles, effectively inhibiting particle aggregation and ensuring stable suspension during the static reaction, resulting in consistent scattering background during absorbance measurements. Furthermore, by adding free polyethylene glycol to the β-cyclodextrin inclusion system, its non-specific interference with the reaction rate is eliminated, improving the relative standard deviation of parallel samples from 5.6% to 2.1%, significantly enhancing detection precision. The spiked recoveries ranged from 98.0% to 98.7%, indicating that the method has good accuracy and repeatability in coal-based ethylene glycol matrix.

[0023] Other advantages, objectives and features of the present invention will become apparent in part from the following description, and in part from those skilled in the art through study and practice of the invention. Attached Figure Description

[0024] Figure 1 The UV-Vis absorption spectrum of the thiolized silica nanoparticles (N1) and indigo color development system of the present invention shows the change in absorbance of the suspension before and after the addition of formaldehyde (10 mg N1 nanoparticles, indigo concentration 0.05 mmol / L).

[0025] Figure 2 This is a standard curve showing the decrease in absorbance (y) of the mercapto-modified silica nanoparticles and indigo suspension of the present invention as a function of formaldehyde concentration.

[0026] Figure 3 This is a comparison of the S2p high-resolution X-ray photoelectron spectroscopy (XPS) of the thiolized silica nanoparticles of the present invention before and after the formaldehyde detection reaction. Detailed Implementation

[0027] The present invention will now be described in further detail to enable those skilled in the art to implement it based on the description. This method uses the difference in absorbance (y=A0-A) before and after the reaction in the same reaction system for quantification. The light scattering background of the nanoparticles themselves can cancel each other out in the two measurements, thus eliminating the need for centrifugation or filtration of the reaction solution. However, it is essential to ensure that the nanoparticles remain in a stable suspension in the system between the measurements of A0 and A, without significant sedimentation (this condition can be met by PEG pre-dispersion in Examples 2 and 3). If an operation without PEG pre-dispersion is used (Example 1), A0 should be measured immediately after the nanoparticles are added, and after the static reaction is completed, the colorimetric tube should be gently shaken to resuspend the sedimented particles before measuring A again, to ensure that the particle scattering background is consistent in both measurements.

[0028] Example 1: Preparation of thiolized silica nanoparticles

[0029] 4.5 g of silica nanoparticles with an average diameter of 15 nm were added to a mixed solvent consisting of 60 mL of acetic acid (HPLC grade), 70 mL of water, and 100 mL of anhydrous ethanol, and stirred to form a nanoparticle suspension. A mixture of 1.63 mmol of 3-[2-(2-aminoethylamino)ethylamino]propyl-trimethoxysilane and 0.1636 mmol of (3-mercaptopropyl)trimethoxysilane was added to the nanoparticle suspension, with a molar ratio of 10:1 for the two silane coupling agents. The reaction mixture was heated to 80 °C and maintained for 48 hours to allow the 3-[2-(2-aminoethylamino)ethylamino]propyl-trimethoxysilane and (3-mercaptopropyl)trimethoxysilane to undergo a hydrolysis-condensation reaction on the surface of the silica nanoparticles, yielding a functionalized nanoparticle suspension. The functionalized nanoparticle suspension was heated and evaporated in a fume hood to remove most of the solvent (or concentrated under reduced pressure using a rotary evaporator to remove the solvent). The precipitate was then collected by centrifugation and washed sequentially with water and acetone. The washed precipitate was dried at 70°C to obtain mercapto-modified silica nanoparticles (designated N1).

[0030] Example 1

[0031] Take 1.0 mL of the coal-based ethylene glycol sample to be tested and place it in a colorimetric tube. Add 10 mg of the mercapto-modified silica nanoparticles N1 prepared in Preparation Example 1 to the coal-based ethylene glycol sample to be tested, and vortex or shake vigorously manually for 1-2 minutes to form a first mixture. Add 1.0 mL of 0.05 mmol / L indigo solution to the first mixture (the volume ratio of the coal-based ethylene glycol sample to the indigo solution is 1:1), mix well, and adjust the pH to 7.4 with phosphate buffer solution to form a second mixture. Immediately after mixing, use a UV-Vis spectrophotometer to measure the initial absorbance A0 of the second mixture at a wavelength of 620 nm. Let the second mixture stand at room temperature (25°C) in the dark or in the dark for 30 minutes, measure the absorbance A after standing, and calculate the difference between the two as the absorbance decrease value y1 (i.e., y1 = A0 - A). Substituting the value of y1 into the linear regression equation between formaldehyde concentration and absorbance, y1=0.7852·c+0.5253, the formaldehyde concentration c in the coal-based ethylene glycol sample to be tested is calculated.

[0032] Example 2

[0033] In this embodiment, the thiolized silica nanoparticles are first dispersed in a polyethylene glycol solution to form a pre-dispersed nanoparticle suspension before being added to the coal-based ethylene glycol sample to be tested. Therefore, the first mixture formed after adding the pre-dispersed nanoparticle suspension to the coal-based ethylene glycol sample to be tested consists of thiolized silica nanoparticles, polyethylene glycol, and the coal-based ethylene glycol sample to be tested, which differs from the first mixture in Example 1 that does not contain polyethylene glycol. The remaining detection steps are the same as in Example 1. Specifically:

[0034] Before adding the thiolized silica nanoparticles to the coal-based ethylene glycol sample to be tested, 10 mg of the thiolized silica nanoparticles N110 prepared in Preparation Example 1 were dispersed in 1.0 mL of a polyethylene glycol solution with a number-average molecular weight of 400 and a mass fraction of 0.3%, forming a pre-dispersed nanoparticle suspension. 1.0 mL of the coal-based ethylene glycol sample to be tested was placed in a colorimetric tube, and 1.0 mL of the pre-dispersed nanoparticle suspension was added to the coal-based ethylene glycol sample to be tested (10 mg of thiolized silica nanoparticles were added per mL of the coal-based ethylene glycol sample to be tested). The mixture was vortexed or vigorously shaken manually for 1–2 minutes to form a first mixture containing thiolized silica nanoparticles, polyethylene glycol, and the coal-based ethylene glycol sample to be tested. This first mixture contained PEG, unlike the first mixture in Example 1 which did not contain PEG. The subsequent steps are the same as in Example 1 (add indigo solution, let stand, measure absorbance, and substitute into the equation y2=0.5235·c+0.3502 to calculate concentration).

[0035] Example 3

[0036] Following the method of Example 2, mercapto-modified silica nanoparticles were pre-dispersed with PEG and added to the coal-based ethylene glycol sample to be tested. Indigo solution was added to form a second mixture. After mixing, the initial absorbance A0 was immediately measured at 620 nm using a UV-Vis spectrophotometer. Subsequently, the second mixture was allowed to stand at room temperature in the dark or in the dark. After standing for 15 minutes, 0.5 mL of β-cyclodextrin solution with a mass fraction of 0.8% was added to the second mixture. The total volume of the second mixture was 3.5 mL (containing 1.0 mL of sample, 1.0 mL of PEG pre-dispersed solution, 1.0 mL of indigo solution, and 0.5 mL of β-cyclodextrin solution). The molar ratio of β-cyclodextrin to PEG in the second mixture was calculated to be approximately 0.47:1 (the amount of β-cyclodextrin added was approximately 0.0035 mmol, and the PEG content in the second mixture was approximately 0.0075 mmol). Continue to allow the mixture to stand for a total of 30 minutes (i.e., 15 minutes after adding β-cyclodextrin, which is sufficient for the inclusion complexation reaction between β-cyclodextrin and polyethylene glycol to reach equilibrium). Measure the absorbance A of the second mixture after standing at 620 nm using a UV-Vis spectrophotometer. Combine this with the previously measured initial absorbance A0 to calculate the absorbance decrease y3 = A0 - A. Substitute the y3 value into the linear regression equation y3 = 0.4487·c + 0.4752 to calculate the formaldehyde concentration c in the coal-based ethylene glycol sample.

[0037] Standard curve and linear relationship:

[0038] In the colorimetric system composed of thiolized silica nanoparticles and indigo, such as Figure 1 As shown, the suspension before the addition of formaldehyde has a stable characteristic absorption peak at a wavelength of 620 nm; after the addition of formaldehyde and standing for 30 minutes, the intensity of the absorption peak at 620 nm decreased significantly, indicating that formaldehyde can induce a specific fading reaction in indigo, and the degree of fading has a quantitative correlation with the formaldehyde concentration.

[0039] For the basic detection system without polyethylene glycol pre-dispersion treatment (corresponding to Example 1), formaldehyde standard solutions with concentrations of 0 ppm, 0.03 ppm, 0.05 ppm, 0.10 ppm, 0.20 ppm, 0.30 ppm, and 0.50 ppm were prepared using formaldehyde-free blank coal-based ethylene glycol as the matrix. Following the procedure in Example 1, the initial absorbance A0 and the absorbance A after static reaction of each concentration standard solution were measured at 620 nm. The difference between the two was calculated to obtain the absorbance decrease value y (i.e., the difference between the initial absorbance before and after the reaction of the same sample, y = A0 - A). A standard curve was plotted with formaldehyde concentration c (unit: ppm) on the x-axis and absorbance decrease value y on the y-axis. The results are shown below. Figure 2 As shown, formaldehyde concentration exhibits a good linear relationship with absorbance decrease in the range of 0.03 ppm to 0.5 ppm. The linear regression equation is: y1 = 0.7852·c + 0.5253, where the intercept 0.5253 represents the background absorbance decrease of the blank sample (formaldehyde concentration of 0) under the same reaction conditions, originating from indigo self-fading and changes in system background. For quantitative calculations, the absorbance decrease, intercept, and slope must be simultaneously substituted into the linear equation to subtract the background, thereby eliminating the interference of inherent system background on the detection results and improving quantitative accuracy. Based on the above linear regression equation, the method detection limit for the basic system is calculated as 0.02871 ppm by dividing the standard deviation (SD) of three times the blank sample signal by the curve slope (i.e., the 3σ / S method).

[0040] For the PEG pre-dispersion detection system (corresponding to Example 2), to match the reagent ratio and total volume of this system, a series of formaldehyde standards were prepared using the same operating sequence and material ratio as in Example 2, and a matching linear regression equation was established: y2 = 0.5235·c + 0.3502. This curve has simultaneously incorporated the effects of PEG matrix and volume dilution, and is used in conjunction with the detection scheme of Example 2. Calculated using the 3σ / S method, the method detection limit of this system is approximately 0.03268 ppm.

[0041] For the detection system of PEG pre-dispersed β-cyclodextrin (corresponding to Example 3), to match the timing of mid-process liquid addition, an equal volume of blank β-cyclodextrin solution was added at the same standing time point as the sample detection when preparing the standard series. This ensured that the standard curve underwent the same volume change and reaction process as the sample, thus establishing a matching linear regression equation: y3 = 0.4487·c + 0.4752. This curve has been calibrated for the dilution effect caused by mid-process liquid addition and is used in conjunction with the detection scheme of Example 3. Calculated using the 3σ / S method, the method detection limit of this system is approximately 0.04013 ppm.

[0042] The three linear regression equations described above were obtained by fitting standard curves established under the specific experimental conditions described in this paper, using reagent ratios and operating sequences completely synchronized with each embodiment. These equations serve as illustrative examples of the quantitative relationship between formaldehyde concentration and absorbance decrease. In actual sample testing, the operating procedures of the corresponding embodiments should be followed to simultaneously establish a standard curve for each batch, in order to eliminate the influence of fluctuations in reagent batches, ambient temperature, and other factors.

[0043] The background absorption of the fixed matrix introduced by the PEG pre-dispersion solution exists in both A0 and A measurements, and can be automatically offset by the difference y=A0-A. The β-cyclodextrin solution is added midway through the standing process, and its background absorption at 620nm is asymmetrical in A0 and A, which cannot be automatically subtracted by the difference. However, this effect has been incorporated into the calibration by the operation of completely synchronizing the standard curve with the sample (adding an equal amount of β-cyclodextrin solution midway), and does not affect the quantitative accuracy.

[0044] XPS characterization:

[0045] The surface chemical state of the mercapto-modified silica nanoparticles prepared in Example 1 before and after the formaldehyde detection reaction was analyzed by S2p high-resolution X-ray photoelectron spectroscopy. The results are as follows: Figure 3 As shown.

[0046] Sample before reaction ( Figure 3 The curve above shows characteristic peaks near the binding energies of 162.58 eV, 163.68 eV, 163.98 eV, and 165.28 eV, which can be fitted as two sets of S2p spin orbital double peaks, mainly belonging to low-valence sulfur-containing species such as surface thiol groups (-SH), Si-S bonds, and disulfide bonds (S-S).

[0047] Thiol-modified silica nanoparticles were reacted with indigo and formaldehyde (0.5 ppm) at pH 7.4 for 30 minutes. The resulting sample was then subjected to S2p high-resolution XPS analysis. Figure 3 (See the curve below). After the reaction, the sample still retains the low-valence sulfur double peaks at 163.88 eV and 165.08 eV, while a new high binding energy double peak appears at 168.28 eV and 169.58 eV, which belongs to S-O type high oxidation state sulfur species (such as sulfoxide and sulfone species).

[0048] The above results indicate that during the formaldehyde-mediated indigo decolorization reaction, some low-valence sulfur on the surface of thiolized silica undergoes oxidative transformation, suggesting that surface thiol groups participate in electron transfer and redox processes within the reaction system. The valence evolution of this sulfur species is consistent with the accelerated indigo decolorization rate after the addition of formaldehyde, providing surface chemical evidence for the participation of thiolized silica nanoparticles in the formaldehyde response process.

[0049] Comparative experiment:

[0050] Comparative experiment between the indigo system and the squaric acid cyanine system:

[0051] Comparative Example 1, Construction of the squaricine system: Squaricine dye was used instead of indigo dye, and other conditions were the same as in Example 1 of this invention. That is, 10 mg of mercapto-modified silica nanoparticles N1 were added to the coal-based ethylene glycol sample, and squaricine dye solution (concentration was the same as that of indigo solution, 0.05 mmol / L) was added. The sample was allowed to stand at room temperature for 30 minutes at pH 7.4, and the absorbance was measured at the maximum absorption wavelength of squaricine.

[0052] Construction of the indigo system: The procedure was performed according to the method described in Example 1 of this invention.

[0053] Experimental method: A standard sample with a formaldehyde concentration of 0.10 ppm was prepared using coal-based ethylene glycol as the matrix. The formaldehyde concentration was determined using both the squaric acid cyanine system and the indigo system of this invention, and the spiked recovery rate was calculated. The results are shown in Table 1.

[0054] Table 1 Comparison of spiked recoveries of the indigo system and squaricine system in coal-based ethylene glycol matrix.

[0055] The results showed that the recovery rate of the scoringin system in the coal-based ethylene glycol matrix was significantly higher than expected, reaching 132.5%, with a relative standard deviation (RSD) as high as 14.6%, indicating that organic background impurities in coal-based ethylene glycol caused serious positive interference to the detection of the scoringin system. In contrast, the indigo system of this invention achieved a recovery rate of 97.8% in the coal-based ethylene glycol matrix, with an RSD of 2.3%, demonstrating that the indigo system of this invention can effectively eliminate the interference of organic background in coal-based ethylene glycol.

[0056] Spiking recovery tests of formaldehyde at different concentrations:

[0057] Following the method in Example 1, formaldehyde standard solutions at low, medium, and high concentrations were added to blank coal-based ethylene glycol samples, resulting in formaldehyde concentrations of 0.05 ppm, 0.15 ppm, and 0.30 ppm, respectively. Each concentration level was measured in parallel five times, and the spiked recovery rate and relative standard deviation (RSD) were calculated. The results are shown in Table 2.

[0058] Table 2. Results of formaldehyde spike recovery tests at different concentrations in coal-based ethylene glycol (Example 1)

[0059] The results show that the method of the present invention has good accuracy and precision, with a spiked recovery rate of 98.0% to 98.7% and an RSD of 1.9% to 2.8% in the concentration range of 0.05 ppm to 0.30 ppm.

[0060] Dispersion stability, precision, and response sensitivity tests of different detection systems:

[0061] I. Comparative test on the dispersion stability of nanoparticles:

[0062] Formaldehyde-free blank reaction systems (referred to as System A, System B, and System C, respectively) were prepared according to the methods described in Examples 1, 2, and 3, with three replicates prepared for each system. The hydration kinetic particle size of the mercapto-based silica nanoparticles in each system was determined using a dynamic light scattering particle size analyzer, and the macroscopic sedimentation state of each system was observed after standing at room temperature in the dark for 30 minutes. The results are shown in Table 3.

[0063] Table 3 Comparison of the dispersion states of nanoparticles in different detection systems

[0064] The results showed that in Example 1, without PEG protection, the nanoparticles in the high-viscosity organic medium of coal-based ethylene glycol exhibited severe agglomeration, with the initial particle size increasing to more than 14 times the original particle size (approximately 15 nm). After standing for 30 minutes, further agglomeration and sedimentation occurred. In contrast, in the systems of Examples 2 and 3, the nanoparticles pre-dispersed with PEG maintained a stable dispersion state close to the original particle size within the same time period. This indicates that PEG effectively suppressed particle agglomeration through steric hindrance.

[0065] II. The enhancement effect of β-cyclodextrin on detection precision:

[0066] Following the procedure of Example 2 (PEG pre-dispersion system), a standard sample with a formaldehyde concentration of 0.10 ppm was prepared under standard operating conditions without the addition of β-CD (i.e., no solution was added during the process, and the total volume was 3.0 mL). Six parallel determinations were performed (n=6), and the RSD value was calculated. Simultaneously, the same concentration of formaldehyde standard samples was determined in parallel (n=6) following the procedure of Example 3 (PEG+β-CD system), and the RSD value was calculated. Both sets of experiments used the same batch number of the coal-based ethylene glycol matrix, the same batch number of the mercapto-modified silica nanoparticles, and the same batch number of indigo reagent. The results are shown in Table 4.

[0067] Table 4 Comparison of detection precision before and after the addition of β-cyclodextrin (formaldehyde concentration 0.10 ppm)

[0068] The results showed that after introducing β-CD, the detection precision (RSD) of the same concentration sample was significantly improved from 5.6% to 2.1%, demonstrating a significant gain. This gain stemmed from the selective inclusion effect of β-CD on free PEG in the system: the uneven distribution of free PEG in the solution led to non-specific weak interactions with the surface of nanoparticles and indigo molecules, causing random fluctuations in the reaction rate; β-CD eliminated the interference of free PEG by forming inclusion complexes with the hydrophobic regions within its cavity and the PEG segments, making the reaction conditions among parallel samples more consistent, thereby effectively reducing the relative standard deviation of the measurement results. Furthermore, it was verified that the β-CD solution had no characteristic absorption at a wavelength of 620 nm (Table 4), therefore its addition would not cause spectral interference to the absorbance measurement of the indigo colorimetric system.

[0069] III. The dilution effect mechanism of the decreasing slope of the three sets of linear equations:

[0070] The slopes of the three linear regression equations were 0.7852 (Example 1), 0.5235 (Example 2), and 0.4487 (Example 3), respectively, showing a decreasing trend. The following verification experiment was designed:

[0071] According to the system composition of Examples 1, 2 and 3, three reaction systems with the same final formaldehyde concentration (0.10 ppm) were prepared (n=3 for each group). The total reaction volume of each system was recorded, and the measured absorbance decrease value (y) was divided by the slope of the standard curve equation of each system to calculate the "slope normalized response value" (y / a, which is theoretically only related to the formaldehyde concentration). The results are shown in Table 5.

[0072] Table 5 Comparison of responses of different detection systems to the same formaldehyde concentration (final concentration 0.10 ppm)

[0073] Table 5 shows that the normalized response values ​​(y / a) obtained by dividing the measured absorbance decrease (y) of each system by the slope (a) of its corresponding standard curve are highly consistent between 0.7684 and 0.7690, with a relative range of less than 0.08%. This result strictly follows the Lambert-Beer law and the basic laws of reaction kinetics—at the same final formaldehyde concentration, the total amount of catalytic decolorization reaction that can occur on the surface of a unit mass of nanoparticles is fixed, and the measured absorbance decrease (y) is directly proportional to the total number of indigo molecules participating in the reaction. The total number of indigo molecules participating in the reaction depends only on the absolute amount of formaldehyde molecules in the reaction system. When the final formaldehyde concentration is the same, each system contains the same absolute amount of formaldehyde; therefore, the normalized reaction signal (y / a) should be consistent.

[0074] The difference in apparent slope among the systems stems from the different total reaction volumes: Example 2 added 1.0 mL of PEG pre-dispersion solution compared to Example 1, diluting the initial molar concentrations of the reactants indigo and formaldehyde to 2 / 3 of their original values ​​(increasing the volume from 2.0 mL to 3.0 mL), resulting in a slope that decreased to 0.5235 / 0.7852 = 66.7%, perfectly matching the theoretical dilution factor of 2.0 / 3.0 = 66.7%; Example 3 further added 0.5 mL of β-CD solution, increasing the total volume from 3.0 mL to 3.5 mL, further decreasing the slope to 0.4487 / 0.7852 = 57.1%, perfectly matching the theoretical dilution factor of 2.0 / 3.5 = 57.1%.

[0075] It is evident that PEG pre-dispersion effectively disperses nanoparticles through steric hindrance, preventing their aggregation and sedimentation in the coal-based ethylene glycol matrix; β-CD eliminates non-specific interference by including free PEG, improving the detection precision (RSD) from 5.6% to 2.1%; the decrease in the slope of the three linear equations was verified by normalization to be caused by the physical dilution effect due to the different total reaction volumes, rather than the difference in detection performance.

[0076] Although the embodiments of the present invention have been disclosed above, they are not limited to the applications listed in the specification and embodiments. They can be applied to various fields suitable for the present invention. For those skilled in the art, other modifications can be easily made. Therefore, without departing from the general concept defined by the claims and their equivalents, the present invention is not limited to the specific details.

Claims

1. A colorimetric method for detecting formaldehyde in coal-based ethylene glycol, characterized in that, Includes the following steps: Thiolized silica nanoparticles are added to the coal-based ethylene glycol sample to be tested. The amount of thiolated silica nanoparticles added is 5 mg to 15 mg per milliliter of the coal-based ethylene glycol sample to be tested, forming a first mixture. An indigo solution with a concentration of 0.04 mmol / L to 0.06 mmol / L was added to the first mixture. The volume ratio of the coal-based ethylene glycol sample to the indigo solution was 1:1 to 2:

1. The mixture was then thoroughly mixed to form a second mixture with a pH value of 7.0 to 8.

0. The initial absorbance A0 of the second mixture was measured at a wavelength of 620 nm using a UV-Vis spectrophotometer. The second mixture was allowed to stand at room temperature for a total of 25 to 35 minutes to allow the formaldehyde in the second mixture to induce a fading reaction in indigo in the presence of the mercapto-modified silica nanoparticles. Measure the absorbance A of the second mixture after it has been allowed to stand, and calculate the decrease in absorbance y = A0 - A; Substituting the absorbance decrease value y into the linear regression equation between formaldehyde concentration and absorbance, the formaldehyde concentration in the coal-based ethylene glycol sample to be tested is calculated. The linear regression equation is y=a·c+b, where y is the absorbance decrease value at a wavelength of 620nm, c is the formaldehyde concentration, a is the slope, and b is the intercept.

2. The method according to claim 1, characterized in that, The thiolized silica nanoparticles were prepared by the following steps: Silica nanoparticles with an average diameter of 10 nm to 20 nm were added to a mixed solvent composed of acetic acid, water, and anhydrous ethanol to form a nanoparticle suspension. The volume ratio of acetic acid, water, and anhydrous ethanol in the mixed solvent was 60:70:

100. The amount of silica nanoparticles used to the mixed solvent was 4.0 g to 5.0 g of silica nanoparticles per 200 mL to 260 mL of the mixed solvent. A mixture of 3-[2-(2-aminoethylamino)ethylamino]propyl-trimethoxysilane and (3-mercaptopropyl)trimethoxysilane is added to the nanoparticle suspension, wherein the molar ratio of 3-[2-(2-aminoethylamino)ethylamino]propyl-trimethoxysilane to (3-mercaptopropyl)trimethoxysilane is 10:1, and 0.30 mmol to 0.50 mmol of 3-[2-(2-aminoethylamino)ethylamino]propyl-trimethoxysilane and 0.030 mmol to 0.050 mmol of (3-mercaptopropyl)trimethoxysilane are added per gram of silica nanoparticles to form a reaction mixture; The reaction mixture is heated to 70°C to 90°C and maintained for 36 to 60 hours to allow 3-[2-(2-aminoethylamino)ethylamino]propyl-trimethoxysilane and (3-mercaptopropyl)trimethoxysilane to undergo a hydrolysis-condensation reaction on the surface of the silica nanoparticles, thereby obtaining a functionalized nanoparticle suspension. The solvent is removed from the functionalized nanoparticle suspension, the precipitate is collected, and the precipitate is washed sequentially with water and acetone. The washed precipitate is then dried at 60°C to 80°C to obtain the thiolized silica nanoparticles.

3. The method according to claim 1, characterized in that, The pH of the second mixture is adjusted to 7.0 to 8.0 using a phosphate buffer solution or a borate buffer solution.

4. The method according to claim 1, characterized in that, Before adding the mercapto-modified silica nanoparticles to the coal-based ethylene glycol sample to be tested, the mercapto-modified silica nanoparticles are dispersed in a polyethylene glycol solution, wherein the number average molecular weight of the polyethylene glycol is 200 to 600, the mass fraction of the polyethylene glycol solution is 0.1% to 0.5%, and the ratio of the mercapto-modified silica nanoparticles to the polyethylene glycol solution is 5 mg to 15 mg of mercapto-modified silica nanoparticles dispersed per milliliter of the polyethylene glycol solution, forming a pre-dispersed nanoparticle suspension; The pre-dispersed nanoparticle suspension is added to the coal-based ethylene glycol sample to be tested, wherein the volume ratio of the pre-dispersed nanoparticle suspension to the coal-based ethylene glycol sample to be tested is 1:1, to form the first mixture.

5. The method according to claim 4, characterized in that, After allowing the second mixture to stand at room temperature for 15 to 20 minutes, a β-cyclodextrin solution with a mass fraction of 0.5% to 1.0% is added to the second mixture, and the molar ratio of the β-cyclodextrin to the polyethylene glycol in the second mixture is 0.2:1 to 2:

1. The mixture is then allowed to stand for a total of 25 to 35 minutes.

6. The method according to claim 1, characterized in that, The linear regression equation is obtained by fitting the standard curve of the batch, and its form is y=a·c+b.